Escuela Ciencias Exacta y Naturales. (UNED, 2024)
De izquerda a derecha de pie de pelo largo al fondo Amalia León Blanco, Lorena Quesada Arce, Olmán Díaz, Flor Montero Jiménez, Ligia Garro Mora, Marvin Campos Moya, Virginia Espeleta Delgado, Walter Arguedas Venegas, María Cascante Prada, Marthas Rivas Rossi, Carlos Urroz Madrigal, sentados de izquierda a derecha Edgar Castillo Cruz de tercero Walter Araya Naranjo y de quinto Gerardo Moreira Ramírez